Manajemen Perubahan untuk Mantan Karyawan: Evaluasi dan Penelitian atas Banyaknya Kegagalan dan Kendala dalam Menjalankan Bisnis Bagi Pemula: Episode 1. Bisnis Adalah Pelayanan dan Solusi Bagi Pelanggan (Konsep Pelayanan Pelanggan) - Puruhita, Prima (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
The most certain thing to happen is change. The passage of time shows the certainty of this change itself, as we have understood that periods of time change episodes need to be addressed properly so that the changes that occur have a beneficial impact. Change always brings uncertainty, but always has patterns that can be learned to reduce the risk of uncertainty itself. For example, during the last pandemic in 2020 - 2022 there were many changes in people's activity patterns which greatly affected work patterns including the emergence of the term "Work From Home" or WFH, and even more extreme changes due to termination of employment or layoffs that companies were forced to do because of changes business situation and condition. This is very important to observe and research, because the situation forces change and because of the responsibilities and demands for the high necessities of life, ideally ex- employees can get a new job in accordance with their field, but it often happens that it is not that easy to get a new job as desired by former employees. This article is an introduction for former employees who want or are forced to change professions as entrepreneurs in order to reduce the risk of failure in dealing with changes in activities and new situations and conditions. So in the full episode the author is also a former International Commercial Bank employee for almost 20 years, namely HSBC and CIMB Niaga. Evaluating and researching the many failures and obstacles in running a business for beginners. For former employees, there are opportunities or opportunities to become self-employed by utilizing available resources as initial capital to initiate changes in new activity patterns at work..  This is the Episode number 1 of total 10 episode. Business is service and solutions for customers (Customer service concept). The definition of customer service or customer service is a service provided by a company that has a duty as a means of consulting, problem solving and information center for each client/customer it has. In Indonesian, Service means service and customers are customers. According to KBBI, service means an effort to serve the needs of others by obtaining rewards.